1994
DOI: 10.1038/sc.1994.31
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric features of wheelchair marathon race competitors with spinal cord injuries

Abstract: The anthropometric data of the health check programme in the Oita Wheelchair Marathon Race were analysed. In the past 10 years, a total of 2677 competitors participated in this programme. Age, height, body weight, body fat, lung vital capacity, girth of chest, girth of upper arm, grasping force and power of upper arm were compared between 710 fine competitors and 99 poor competitors. Power of the upper arms and lung vital capacity played a major part in the result of the races. It was suggested that these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Longitudinal body composition studies in persons with SCI are few, missing time points, and small in numbers (44). Several investigators have used cross-sectional designs with relatively small sample sizes to compare body composition changes and/or dif ferences in chronic SCI with control subjects (12,27,35,41).…”
mentioning
confidence: 99%
“…Longitudinal body composition studies in persons with SCI are few, missing time points, and small in numbers (44). Several investigators have used cross-sectional designs with relatively small sample sizes to compare body composition changes and/or dif ferences in chronic SCI with control subjects (12,27,35,41).…”
mentioning
confidence: 99%
“…We assume that skeletal muscle mass is the link for these findings. The power of the upper arms and lung vital capacity played a major part in performance in wheelchair cyclists in the 'Oita Wheelchair Marathon Race' (Ide et al, 1994). Wheelchair athletes can only use the muscles of their upper body (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with BMI, more variability of the data exists in %BF across the studies. In the reviewed studies, the most common methods used to estimate %BF were DXA 9,21-24 and SFK, 17,20,25,26 followed by HW 16,18,19 , along with TOBEC 37 and 40K. 18 Several studies in The results of these studies may indicate that regular physical activity is effective in improving body composition of adults with physical disabilities, as this relationship has been demonstrated in the general population.…”
Section: Physical Activity On Body Compositionmentioning
confidence: 99%
“…36 On the other hand, two studies reported low %BF (15.6 and 17.4%, respectively) of competitive/elite athletes with SCI or poliomyelitis. 25,37 Ide et al 26 conducted anthropometric measurements, including %BF, of more than 800 wheelchair marathon racers for 10 years. The study found an average %BF of 18.1-18.4%, even though the gender of the racers is not specified.…”
Section: Physical Activity On Body Compositionmentioning
confidence: 99%